PUBLIC EARLY CHILDHOOD EDUCATION AS A COMMODITY IN THE WESTERN CONTEXT - Lopes, Laís dos Santos; Santos, Solange Mary Moreira (Literatura em Debate, 2025)
This article, the result of ongoing research, aims to problematize public Early Childhood Education in its interface with the State in the Western context, considering that the imperative of neoliberal reason subjectively guides all spheres that make up the capitalist world, that is, also public Early Childhood Education with all the children that permeate it, the adults that surround them, as well as the political society responsible for offering this right and social (public) policy. The study is of a qualitative nature, constituting part of a documentary research within the scope of the academic master's degree, methodologically guided by the criteria of bibliographic review. The results corroborate the axiom that neoliberal rationality treats public Early Childhood Education as a commodity, in view of the four pillars evidenced in the business counter: privatization, the technocracy of austerity, the production of neoliberal subjects and the feeling of unnecessary public service.